Financial Influences Linked to Hearing Aid Purchases - Windmill, Ian M. (Seminars in Hearing, 2025)
One of the factors that is presumed to influence the decision to obtain hearing aids is the cost of the product. The MarkeTrak 2025 surveyed individuals on a variety of factors about their decision to seek, or not seek, amplification, including the financial implications. The survey included 1,173 hearing aid owners, either prescription or over-the-counter (OTC) devices, and 1,782 non-owners of hearing aids. Key financial factors identified in the survey included differences in demographics between those choosing prescription hearing aids and OTC devices, the impact of insurance coverage on decision to pursue amplification, and the continued conflation of hearing care with hearing aids. Owners of prescription hearing aids tended to be older, white, and had higher income levels. Conversely, owners of OTC devices were younger, still working, included more non-white individuals, and had lower income levels. Non-owners are demographically similar to those individuals who chose OTC devices.
Keywords: cost; hearing aids; over-the-counter; insurance